2016
DOI: 10.1111/aphw.12061
|View full text |Cite
|
Sign up to set email alerts
|

Within‐Person Link between Depressed Affect and Moderate‐to‐Vigorous Physical Activity in Adolescence: An Intensive Longitudinal Approach

Abstract: This study encourages the development of individually tailored physical activity interventions that could help adolescents enhance their daily amount of unstructured, self-initiated MVPA to reduce depressed affect. This approach may be particularly suitable for young women who have the highest risk for an inactive lifestyle and elevated depressed affect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
1
12
0
3
Order By: Relevance
“…The negative association between physical activity and unpleasant-deactivated core affects, at the within-and between-person level, are also in line with previous findings (e.g., Langguth et al, 2016). Other studies have, however, found mixed support for the relationship between physical activity and unpleasant-deactivated core effects (Liao et al, 2015(Liao et al, , 2017.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The negative association between physical activity and unpleasant-deactivated core affects, at the within-and between-person level, are also in line with previous findings (e.g., Langguth et al, 2016). Other studies have, however, found mixed support for the relationship between physical activity and unpleasant-deactivated core effects (Liao et al, 2015(Liao et al, , 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have, however, reported inconsistent and inconclusive findings for the influence of physical activity on unpleasant core affects (Liao et al, 2015) and the general pattern in previous research is that physical activity has a more pronounced effect on positive affect than negative affect (Liao et al, 2017;Mata et al, 2012;Wichers et al, 2012). Although, recent findings suggest that daily moderate to vigorous psychical activity can decrease the level of depressed and angry affects in the evening in adolescents and young adults (Haas et al, 2017;Langguth et al, 2016).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Studies in adults suggest that it is plausible that the chronic effects of PA may be related to or represent a summation of acute effects of single bouts of activity [21]. However, an assessment of German adolescents suggests that a daily increase in moderate-to-vigorous PA reduces mood disturbance the day after, but not the evening of, an increase in PA, potentially implicating sleep quality on active days as a mediating factor [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Instead of grouping people into more or less active groups, we aimed at relating within-person variations in physical activity to within-person variations in depressive mood. So far, very few studies examined within-person associations between physical activity and depressive mood, or more broadly, affect in everyday life using intensive longitudinal designs, and these studies typically focused on samples of younger adults (e.g., Bossmann, Kanning, Koudela-Hamila, Hey, & Ebner-Priemer, 2013;Kanning & Schlicht, 2010;Langguth, Schmid, Gawrilow, & Stadler, 2016;Reichert et al, 2016;Schwerdtfeger, Eberhardt, Chmitorz, & Schaller, 2010). For example, a recent study investigated within-person associations between physical activity and affect in younger adults over 10 consecutive days (Haas, Schmid, Stadler, Reuter, & Gawrilow, 2017).…”
Section: Physical Activity and Depressive Moodmentioning
confidence: 99%